Manajemen Kebijakan Program Pendidikan di SD IT Al-Anshar Tanjung Pura - Yuria Nadila; M. Yusuf Abdullah; Ahmad Zaki (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to explore the policy management of educational programs at SD IT Al-Anshar Tanjung Pura in integrating the national curriculum with Islamic values. The research approach used is qualitative with a descriptive method, involving observation, interviews, and documentation as data collection techniques. The subjects of the study include principals, teachers, and students, while the object is the education management policy in this school. The results of the study show three main findings: 1) Policy planning is designed to form a generation that excels in academics and has Islamic character through careful planning that involves all parties. 2) The implementation of policies prioritizes a balance between religious and general education, supported by collaboration between teachers, students, and parents, as well as various extracurricular activities. 3) Policy evaluations are carried out regularly to measure the success of educational programs even though they still face the challenge of limited resources. This study emphasizes the importance of the role of planning, collaborative implementation, and regular evaluation in education policy management to achieve holistic educational goals.